2020
DOI: 10.1111/ene.14535
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of acute stroke among patients with severe COVID‐19: a multicenter study and meta‐analysis

Abstract: Background and purpose Recent observations linked coronavirus disease 2019 (COVID‐19) to thromboembolic complications possibly mediated by increased blood coagulability and inflammatory endothelial impairment. We aimed to define the risk of acute stroke in patients with severe and non‐severe COVID‐19. Methods We performed an observational, multicenter cohort study in four participating hospitals in Saxony, Germany to characterize consecutive patients with laboratory‐confirmed COVID‐19 who experienced acute str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 21 publications
(24 reference statements)
4
58
0
2
Order By: Relevance
“…The overall incidence of ischemic stroke of 1.8% in hospitalized patients with COVID-19 is in line with previously published hospital-based COVID-19 cohorts, which reported cumulative incidences ranging between 1.0% and 2.4%. [3][4][5] Lower stroke rates have been found in studies that reported on a combination of hospitalized and non-hospitalized patients. 6,23 Higher rates of up to 6.9% have been reported in populations consisting of ICU patients alone or in other selected patient populations.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…The overall incidence of ischemic stroke of 1.8% in hospitalized patients with COVID-19 is in line with previously published hospital-based COVID-19 cohorts, which reported cumulative incidences ranging between 1.0% and 2.4%. [3][4][5] Lower stroke rates have been found in studies that reported on a combination of hospitalized and non-hospitalized patients. 6,23 Higher rates of up to 6.9% have been reported in populations consisting of ICU patients alone or in other selected patient populations.…”
Section: Discussionmentioning
confidence: 98%
“…First, most studies were performed in Asia and North America, with only a few European cohorts. [3][4][5]7 Geographical variation may explain some of the heterogeneity, with a higher incidence reported in Asia than in North America and Europe. 3 In addition, regional differences in COVID-19 surges may have resulted in a higher threshold for seeking medical attention in some pandemic areas, especially for patients with mild symptoms of stroke.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pathophysiologisch könnte dies auf direkte negative Auswirkungen der Immunreaktion, die Beschleunigung oder Aggravation bereits bestehender kognitiver Defizite oder sogarwie von einigen Forschern vermutetauf die De-novo-Entstehung einer neurodegenerativen Erkrankung zurückzuführen sein [37]. Auch akute zerebrale Ischämien finden sich bei COVID-19-Patienten häufiger [38].…”
Section: Langzeitfolgen Nach Covid-19unclassified